Projection of Precipitation Extremes and Flood Risk in the China–Pakistan Economic Corridor - Du, Shixiong; Wu, Ruiying; Sun, Huaiwei; Yan, Dong; Xue, Jie; Liao, Weihong; Tuo, Ye; Zhang, Wenxin (Frontiers in Environmental Science, 2022)
It is reported that the China-Pakistan Economic Corridor (CPEC) has been affected by extreme precipitation events. Since the 20th century, extreme weather events have occurred frequently, and the damage and loss caused by them have increased. In particular, the flood disaster caused by excessive extreme precipitation seriously hindered the development of human society. Based on Criteria Importance Though Intercrieria Correlation (CRITIC) and Square Root of Generalized Cross-Validation (RTGCV), this study used Intensity-Area-Duration (IAD) to analyze the trend of future extreme precipitation events, corrected the Equidistance Cumulative Distribution Function Method (EDCDFm) deviation of different future scenario models (CESM2, CNRM-CM6-1, IPSL-CM6A-LR, MIROC6) and evaluated the simulation ability of the revised model. The results showed that: (1) the deviation correction results of CNRM-CM6-1 in CMIP6 could better simulate the precipitation data in the study area, and its single result could achieve the fitting effect of the CMIP5 multi-model ensemble average; (2) Under CNRM-CM6-1, the frequency of extreme precipitation events under the three combined path data (SSP1-2.6, SSP3-7.0, and SSP5-8.5) presents interdecadal fluctuations of 3.215 times/10A, 1.215 times/10A and 5.063 times/10A. The average impact area of extreme precipitation events would decrease in the next 30 years, while the total impact area and the extreme precipitation events in a small range would increase. Under the future scenario, the increase rate of extreme precipitation in August was the fastest, which increased the probability of extreme events; (3) In the next 30 years, the flood risk had an obvious expansion trend, which was mainly reflected in the expansion of the area of high, medium and low-risk areas. The risk zoning results obtained by the two different flood risk assessment methods were different, but the overall risk trend was the same. This study provided more advanced research for regional flood risk, reasonable prediction for flood risk under future climate models, and useful information for flood disaster prediction in the study area, and contributes to the formulation of local disaster prevention and reduction policies.